N‐terminal pro brain natriuretic peptide reference values in community‐dwelling older adults - Ulrike Braisch; Wolfgang Koenig; Dietrich Rothenbacher; Michael Denkinger; Nele Friedrich; Stephan B. Felix; Till Ittermann; Marcus Dörr; Dhayana Dallmeier (ESC Heart Failure, 2022)
Abstract Aims Available upper reference levels (URLs) in older adults for N‐terminal pro brain natriuretic peptide (NT‐proBNP), an established biomarker for heart failure, are mainly based on small samples. We aimed to identify NT‐proBNP URL in a population‐based reference sample of individuals aged ≥65 years. Methods and results We analysed established NT‐proBNP predictors using quantile regression among 2459 participants of two‐independent population‐based cohorts located in Germany, the Activity and Function in the Elderly Study (ActiFE, n = 1450) and the Study of Health in Pomerania (SHIP‐TREND‐0, n = 1009). Based on predictors a reference population of 441 subjects (ActiFE, n = 227; SHIP‐TREND‐0, n = 214) without history of diabetes, cardiovascular, or pulmonary diseases and with systolic blood pressure (BP) <140 mmHg, diastolic BP ≥60 and ≤90 mmHg, haemoglobin in men ≥14 and ≤18 g/dL and in women ≥12 and ≤16 g/dL, GFR ≥60 mL/min/1.73 m2, CRP <5 mg/L, BMI ≥18 and ≤33 kg/m2, and hs‐cTnI <40 ng/L were built with NT‐proBNP median levels and 97.5% quantiles reported stratified by sex and age. In a secondary analysis the URL among 97 SHIP‐TREND‐0 participants with a left ventricular ejection fraction (LVEF) ≥50 and no diastolic dysfunction were estimated. The median age in the identified reference sample was 70 years, with 41.9% and 40.2% male participants in ActiFE and SHIP‐TREND‐0, respectively. We observed an age‐dependent increment of NT‐proBNP levels with higher values in women compared to men. Notably, NT‐proBNP levels were >125 ng/L in 165 participants (37.4%), with NT‐proBNP URL (97.5% quantiles) equal to 663, 824, 592, and 697 ng/L in men, and 343, 463, 2641, 1276 ng/L in women for ages 65–69, 70–74, 75–79, and 80+ years, respectively. In the secondary analysis with a LVEF ≥50 and no diastolic dysfunction (35 men and 62 women) NT‐proBNP levels >125 ng/L were still observed in 38 (39.2%) participants. Conclusions This reference sample of apparently healthy asymptomatic older adults showed an age‐related increment of NT‐proBNP levels with URL markedly higher than the European Society of Cardiology recommended cut‐off of 125 ng/L for the diagnosis of heart failure in ambulatory settings. Identifying URL in those ≥80 years remains complex. Our results attempt to provide a frame for the further investigation of age‐specific NT‐proBNP cut‐offs in older adults. Considering the demographic changes, further evaluation of NT‐proBNP URL in larger samples of older adults followed by the validation of age‐specific cut‐off values for the identification of heart failure in those 65 years or older are urgently needed.